Crisis risk in the 21st century and their impact on the banking sector - Vesić Tamara; Petronijević Jovan; Ravić Nenad (Trendovi u Poslovanju)
Just over a decade after the outbreak of the global economic crisis in 2008, the world is once again facing a global crisis caused by the Covid-19 virus pandemic. The paper compares the effects of the crisis on the banking sector with special reference to the measures of the National Bank of Serbia that were implemented in order to preserve financial stability in the Republic of Serbia. It was concluded that the Serbian banking sector has consistently submitted to the moratorium introduced by the NBS, most likely as a consequence of high liquidity and capital adequacy in previous periods. On the other hand, due to the corona virus pandemic, many factories have stopped producing gold, the transport of goods is functioning slowly, which has led to a shortage of gold, so it is almost impossible to buy a gold ducat or gold bar in Europe. As a result, the jump in demand consequently affected the increase in the value of gold. Although bankers quickly adapted to work from home and electronic delivery of services to end users, what is a fact is that in the future we will certainly face new financial shocks, so one of the goals of the work is to create foundations and recommendations for further business research in risky situations.